Criticality, Depth and Voice in Academic Writing - Bastola, Madhu Neupane (Tribhuvan University Journal, 2016)
Academic writing plays a crucial role in academic as well as professional life of learners. Developing academic writing takes long time and efforts. Though there are multiple factors that play the role of enablers or disablers for success in academic writing, awareness of basic characteristics of academic writing is a fundamental prerequisite. Similarly, the requirements of academic writing differ from culture to culture and institution to institution. Therefore, it is highly important for learners to understand the expectations of academic writing in their institutions. This article describes an ethnographic study that was conducted in the University of Sydney, Australia to understand a course coordinator’s expectation regarding criticality, depth and voice in academic writing. To answer the research question raised in the study, data were collected from published and unpublished secondary sources, an interview coordinator of the of course Second Language Acquisition (SLA) and an assignment in SLA. The thematic analysis of data revealed that criticality, depth and voice are important characteristics of academic writing. Different ways to meet the expectation of criticality, depth and voice are discussed and some suggestions for further research are forwarded based on the discussion.